Comparison Of Thermo Gravimetric Characterization Of Active Carbon Analyzer Rice Husk With Rice Husk Implementation - Zurairah, Masdania; Saragih, Edy Syahputra; Misdawati, Misdawati (Jurnal Matematika Dan Ilmu Pengetahuan Alam LLDikti Wilayah 1 (JUMPA), 2021)
Research has been done on rice husks. Rice husk is carried out in the carbonization process which is then carried out by the activation process. Furthermore, from the activation process, the impregnation process is carried out. Characterization using a thermo gravimetric analyzer (TGA) showed that the residue of impregnation of rice husk activated carbon was 61.83% and rice husk activated carbon was 89.72%.